2010
DOI: 10.1016/j.neuroimage.2009.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Processing speed is correlated with cerebral health markers in the frontal lobes as quantified by neuroimaging

Abstract: We explored relationships between decline in cognitive processing speed (CPS) and change in frontal lobe MRI/MRS-based indices of cerebral integrity in 38 healthy adults (age 57–90 years). CPS was assessed using a battery of four timed neuropsychological tests: Grooved Pegboard, Coding, Symbol Digit Modalities Test, and Category Fluency (Fruits and Furniture). The neuropsychological tests were factor analyzed to extract two components of CPS: psychomotor (PM) and psychophysical (PP). MRI-based indices of cereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
113
2
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(132 citation statements)
references
References 81 publications
15
113
2
2
Order By: Relevance
“…There is evidence that late‐myelinating white matter is more susceptible to the age‐related degeneration (Bartzokis, 2004), thus our data may capture this process by showing that older individuals rely more on the integrity of such incipiently deteriorating WM tracts. Overall, our results are well in line with earlier reports on the role of white matter integrity in cognitive processing speed (Kochunov et al, 2010) and more in general executive functions (Borghesani et al, 2013; Kochunov et al, 2009), and further extend previous findings to the macrostructural properties of white matter fiber bundles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…There is evidence that late‐myelinating white matter is more susceptible to the age‐related degeneration (Bartzokis, 2004), thus our data may capture this process by showing that older individuals rely more on the integrity of such incipiently deteriorating WM tracts. Overall, our results are well in line with earlier reports on the role of white matter integrity in cognitive processing speed (Kochunov et al, 2010) and more in general executive functions (Borghesani et al, 2013; Kochunov et al, 2009), and further extend previous findings to the macrostructural properties of white matter fiber bundles.…”
Section: Discussionsupporting
confidence: 93%
“…To this respect, previous studies reported that reduced processing speed was related to impaired white matter, as indexed by both micro and macrostructural integrity (Borghesani et al, 2013; Kochunov et al, 2010). In another study, Kochunov et al (2009) further demonstrated a positive association between white matter span and executive control.…”
Section: Introductionmentioning
confidence: 96%
“…Consistently, functional MRI studies have suggested that a distributed brain network subserves processing speed, including the prefrontal, occipital, temporal, and parietal cortices (for review, see Deary et al, 2010). Both white matter volume and GMV in those regions were also associated with processing speed (Kochunov et al, 2010); age-related processing speed decline was associated with decreased gray matter density in the prefrontal regions, temporal lobe, and posterior parietal cortex (Tisserand et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Scientifically, it was chosen because it consistently shows significant schizophrenia-related WM deficits (33,44,45). The corpus callosum was also chosen because it is composed of commissural fibers that facilitate long-interhemispheric signal transmission and shows strong phenotypic and genetic associations with processing speed in humans and primates (46)(47)(48)(49). In addition, the corpus callosum provides the feasibility needed for testing the specific hypothesis.…”
Section: Methodsmentioning
confidence: 99%